Systematic Literature Review: Gamification in Educational Media for Islamic Schools (2015-2025) - Biabdillah, Fajerin; Tajuddin, Muhammad; Awaluddin A., Muhammad; Maknuniah, Jauharatul; Maesaroh, Dwi Titi (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2025)
This systematic literature review synthesizes research on gamification in educational media for Islamic education conducted between 2015 and 2025. Using PRISMA guidelines, 32 peer-reviewed studies were selected from 112 records, comprising 14 quantitative studies (including 6 quasi-experimental and 2 controlled designs), 11 qualitative or design-based studies, and 7 review or mixed-method studies. Most research was conducted in Islamic primary and secondary schools, with limited evidence from Islamic higher-education institutions. Overall, the majority of studies report increased student engagement and learning motivation following the integration of gamification elements such as points, badges, leaderboards, levels, and interactive quizzes. Evidence on academic and religious learning outcomes is more mixed: several experimental studies show moderate improvements in test scores, Quranic literacy, or language learning, while others report no significant gains beyond motivation. Gamification implementations are largely mechanics-driven and commonly supported by instructional design models such as ADDIE, with few frameworks explicitly tailored to Islamic educational values. Recurring challenges include limited digital infrastructure, insufficient teacher training, curriculum alignment constraints, and concerns regarding cultural and religious appropriateness. The review concludes that gamification is effective for enhancing engagement in Islamic education, but its impact on learning outcomes remains context-dependent.